Optimizing the Recovery of Corrupt Assets from the Perspective of Economic Rights and Human Security in Indonesia - Ronald Hasudungan Sianturi (UIN Sunan Gunung Djati, 2025)
This study aims to analyze the optimization of corrupt asset recovery in Indonesia through the revision of the replacement money policy. The current policy, which is regulated in Indonesia’s anti-corruption criminal law, often faces implementation challenges, such as difficulties in tracing and confiscating assets and the minimal amount of assets recovered compared to the total state losses. These weaknesses reduce the effectiveness of asset recovery and weaken the deterrent effect on corruption perpetrators. The research uses a normative legal method with a statutory and comparative approach. Legal provisions related to the replacement money policy in Indonesia are reviewed and compared with best practices from other countries that have implemented more effective asset recovery mechanisms, and the analysis also involves legal interpretation and evaluation of policy implementation in corruption cases. The results show that revising the replacement money policy is urgently needed to enhance the legal framework and enforcement mechanism. Strengthening the execution process, improving the clarity of confiscation procedures, and encouraging the use of digital tracing technologies and institutional collaboration can significantly increase the effectiveness of asset recovery. This policy reform is expected to provide a stronger deterrent effect, support transparency and accountability in law enforcement, and contribute to sustainable anti-corruption efforts in Indonesia.